Oral Administration of Acidophilus Milk Supplemented with Calcium Pyruvate Modulates some Biochemical Parameters and Weight Gain in Rats Fed High Fat Diet - Elshaghabee, Fouad Mahmoud Fouad (Indian Journal of Dairy Science, 2019)
This study aims to evaluate the protective effect of acidophilus milk supplemented with calcium pyruvate on reduction of obesity in rat model. For that purpose, Albino rats were randomized into three groups; rats in the first group (I, control) were fed high fat diet while rats in experimental groups were fed the same diet and orally administrated with acidophilus milk or acidophilus milk supplemented with 3 % of calcium pyruvate for rats in group III. After five weeks of intervention, levels of plasma triglycerides, cholesterol, glucose, liver markers, and IL-6 and body weight were significantly (p < 0.05) increased in rats of group I compared to rats in both experimental groups. Also, levels of plasma IL-10 were significantly increased in the experimental groups compared to rats in groupÂ I. Results of this study indicated that supplementation of acidophilus milk with calcium pyruvate could decrease the weight gain and modulate plasma triglycerides, cholesterol, glucose, liver markers, IL-6and IL-10 in rat model. Indeed, further research on the molecular mechanism of anti-obesity effect of calcium pyruvate is still needed.